Epileptic seizures due to multiple cerebral cavernomatosis - Spasić Mirjana; Lukić Stevo (Vojnosanitetski Pregled)
Background. Cavernous angiomas are angiographically occult vascular malformations that are present in 0.4−0.9 % of people, and represent around 5% of all cerebrovascular malformations. They can be single or multiple, and sporadic or familial. The presence of multiple lesions is more frequent in familial cavernomatosis. Ten to 30 % are associated with familial clustering. Case report. We presented the case of a 43-year-old man, admitted to the Emergency Department due to unprovoked seizure during the wide awake and everyday activities. Neurological examination was with no focal signs. A 32-channel standard digital EEG was without any significant changes of normal baseline activity. After sleep deprivation EEG showed multifocal, bilateral and asymmetric polyspikes and sharpwaves activity. Hyperventilation induced generalized epileptiform discharges. MRI scan demonstrated multiple small cavernous angiomas. Neuropsychological testing demonstrated a delayed memory impairment. Neurosurgery treatment was not recommended, and the therapy with valproate 1 250 mg/day had an excellent efficacy with no singnificant adverse effects. Conclusion. This patient considered as a rare case with multiple cavernomatosis highlights the importance of neuroradiological examination in adult patients with the first epileptic seizure but with no focal neurological signs. .